Polymer actuator valves toward controlled drug delivery application - Xu, H.; Wang, C.; Wang, C.; Zoval, J.; Madou, M.
A novel controlled drug delivery system in which drug release is achieved by electrochemically actuating an array of polymeric valves on a set of drug reservoirs has been developed. The valves are bilayer structures, made in shape of a flap hinged on one side to a valve seat, consisting of thin films of evaporated gold and electrochemically deposited polypyrrole (PPy). Drugs (dry or wet)were pre-stored in an array of these reservoirs and their release is accomplished by bending the bilayer flaps away from the substrate with a small applied bias. In vitro color dye release experiment has been conducted. Seventy-five percent less energy consumption was achieved with this bilayer polymer valve design to open a same size reservoir compared to metal-corrosion based valves. Complex release patterns such as multiple drug pulsatile release and continuous linear release have been successfully implemented through flexible control of valve actuation sequence. These valves can be actuated under closed-loop-control of sensors responding to a specific biological or environmental stimulus, leading to potential applications in advanced responsive drug delivery systems.
Keywords: POLYMER ACTUATOR; VALVE; POLYPYRROLE; DRUG DELIVERY